Consumption Patterns and Perception Of Instan Chocolate Powder Drinks From Local and Imported Products in The Border Region - Akbar, Dzifiar Yasykuri; Adawiyah, Dede Robiatul; Hunaefi, Dase (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2025)
This study aims to analyze the perceptions and consumption patterns of instan chocolate powder drinks in two border cities, namely Batam City and Pontianak City, both local and imported products. The method used was a questionnaire-based survey distributed to 100 respondents in each city. Data were analyzed using IBM SPSS Statisctics 25 software with a significance level of 5% to identifiy the factors influencing consumer perferences in choosing instant chocolate powder drink products. The results of the study indicate that respondent characteristics, such as gender, age, marital status, education level, and occupation, influence perceptions and consumption patterns among individuals in both regions. Respondents in Pontianak City tend to choose local products by considering price and the benefits offered by the product, while respondents in Batam City priotize quality and packaging. Consumption patterns in both regions are relatively low, with a frequency of once a month. Most respondents in this study chose locally produced instant chocolate powder drinks because they are more economical, of higher quality, and have a stronger brand image compared to imported products. Age, marital status, and education level influence respondents' preferences. This is evidenced by the fact that married respondents tend to consider health and economic aspects more when choosing products, while unmarried respondents are more influenced by trends and convenience. The results of this study can serve as a basis for local producers to enhance the competitiveness of local products in the domestic market, particularly in border areas with access to imported products.